The Effect of Financial Performance, Thin Capitalization, and Capital Intensity on Tax Avoidance: A Different Analysis on Foreign Ownership - Neng Aprianti; Deden Tarmidi (LifeSciFi, 2025)
Indonesia’s persistently low tax ratio, coupled with widespread tax avoidance practices, highlights the urgency of examining how corporate financial performance, capital structure, and ownership influence tax avoidance behavior. This study aims to analyze the influence of financial performance, thin capitalization, and capital intensity on tax avoidance by analyzing differences in foreign ownership. The research sample consists of 56 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period, with a total of 56 samples. The research method uses a quantitative approach with panel data regression. The results of the study show that financial performance has a positive and significant effect on tax avoidance in companies with foreign ownership. Thin capitalization has a negative on tax avoidance in companies without foreign ownership, but it has no effect on companies with foreign ownership. Capital intensity has a negative effect on tax avoidance in companies without foreign ownership, while it has no effect on companies with foreign ownership. These findings show that there are differences in tax avoidance strategies between companies with foreign and non-foreign ownership.